Global research dynamics in the Tai Chi and insomnia: a bibliometric study from 2006 to 2025 - Liao, Mo (Frontiers in Psychiatry, 2025)
ObjectiveTai Chi has demonstrated beneficial effects in managing insomnia. However, no bibliometric analysis has systematically examined the relationship between Tai Chi and insomnia. This study aims to quantitatively evaluate the global research landscape and emerging trends related to “Tai Chi and insomnia” from 2006 to 2025 using bibliometric methods, thereby offering evidence-based insights and guidance for future basic and clinical research.MethodsA bibliometric analysis was conducted using data retrieved from the Web of Science Core Collection (WoSCC)) and Scopus databases for the period 2006–2025. The data were processed and visualized using Bibliometrix (R software), VOSviewer, and CiteSpace.ResultsA total of 281 valid articles from the WoSCC and 489 from Scopus were included. The number of publications on Tai Chi and insomnia has steadily increased over the past two decades. China and the United States are the primary contributors to research in this field, forming an international collaboration network centered around the University of California, Los Angeles (UCLA) and the University of Hong Kong. Among them, Professor Michael R. Irwin from UCLA is the most prolific author and maintains the widest collaborative network in this domain. Frontiers in Psychiatry and Sleep Medicine Reviews show the highest publication volumes, whereas Sleep ranks first in citation frequency and functions as a key hub for academic collaboration. Using cluster analysis, keyword frequency assessment, co-word mapping, and thematic evolution analysis, we identified several prominent research hotspots. These hotspots primarily focus on three areas: the clinical application and efficacy evaluation of Tai Chi in specific patient populations with sleep disorders, mechanistic and evidence-based investigations of Tai Chi interventions for insomnia, and comparative or integrative studies of Tai Chi with other non-pharmacological treatments for insomnia.ConclusionThe therapeutic potential of Tai Chi for insomnia has garnered growing global interest and is poised to become a major focus in insomnia management. This study provides a comprehensive overview of the field’s current status and key research trends, offering valuable direction for future studies.